Telaah Hakikat Filsafat Pendidikan Islam: Konsep, Tujuan Dan Fungsi, Serta Peran Filsafat Dalam Pendidikan Islam - Mulyani, Nova; Islamiyyah, Novita Dyah; Sari, Herlini Puspika (EL-EMIR Institute, 2024)
This study investigates the basic principles of Islamic educational philosophy, focusing on its components philosophy, education, and Islam and their integration in forming a holistic educational approach. The main research question examines how philosophical doctrine influences the goals and practices of Islamic education. Positioned within the framework of classical Islamic thought, this research uses library-based qualitative methods, analyzing various texts and previous research to understand the philosophical foundations of Islamic education. The findings reveal that Islamic educational philosophy emphasizes intellectual, spiritual and moral development, which aims to produce individuals who are balanced and adhere to Islamic values. This study highlights the importance of integrating philosophical principles to maintain coherence with Islamic teachings, enabling education to address modern challenges and traditional values ​​effectively.